2021
DOI: 10.1021/acsanm.1c01046
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dots as Fluorescence Nanochemosensors for Selective Detection of Amino Acids

Abstract: Fluorescent carbon quantum dots (CDs) are synthesized and employed as fluorescent nanochemosensors for selective detection of amino acids. A detailed investigation of excitation−emission maps revealed that the fluorescence properties of CDs are intensely and strongly influenced by the interaction at the surface with different amino acids. The discrimination capability was demonstrated by tensor rank decomposition of the differences induced by the surface reaction in the excitation−emission maps and by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…The typical concentration of the 'as prepared' solution is around 2 mg/mL. For characterization of CDs and related instrumentation, see article [35].…”
Section: Methodsmentioning
confidence: 99%
“…The typical concentration of the 'as prepared' solution is around 2 mg/mL. For characterization of CDs and related instrumentation, see article [35].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Tuccitto and co-workers reported the preparation of fluorescent CNPs as a fluorescent sensor for the selective detection of amino acids. 85 In particular, the analysis of the excitation–emission bidimensional maps showed that the CNP emission properties were strictly related to the interactions between the nanoparticle surface and the amino acids ( Fig. 12 ).…”
Section: Cnps For Chemical Sensingmentioning
confidence: 99%
“…Tuccitto et al synthesized a fluorescent nanosensor, based on carbon nanoparticles (CNPs) which was covalently functionalized with ethanolamine arms for interaction with nerve agents [171]. Again Tuccitto et al synthesized a fluorescence CDs nanochemosensor, for the selective detection of amino acids [26]. Tuccitto et al, also developed functionalized CDs, for the supramolecular sensing of the chemical warfare agents' simulants [28].…”
Section: Applications Of Cds In Chemical Warfarementioning
confidence: 99%
“…The most recent application of CDs is in the field of chemical warfare agents, especially for the detection of hazardous chemicals. These CDs were used either functionalized and non-surface modified forms which was reported by Kumar [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%